Combatting insects mediated biotic stress through plant associated endophytic entomopathogenic fungi in horticultural crops - Samal, Ipsita; Bhoi, Tanmaya Kumar; Majhi, Prasanta Kumar; Murmu, Sneha; Pradhan, Asit Kumar; Kumar, Dilip; Saini, Varun; Paschapur, Amit Umesh; Raj, M Nikhil; Ankur,; Manik, Suryakant; Behera, Partha Pratim; et al. (Frontiers in Plant Science, 2023)
Horticultural production is a vital catalyst for economic growth, yet insect infestations reduce horticultural crop yield and quality. Pesticides and other pest control methods are used during planting to eliminate pests that cause direct and indirect losses. In such situations, endophytic entomo-pathogenic fungi (EEPF) can act as potential tool for biological control. They protect plants by boosting growth, nutrition, morpho-physiology and salt or iron tolerance. Antixenosis, antibiosis and plant tolerance change insect performance and preferences. EEPF- plant colonisation slows herbivore development, food consumption, oviposition and larval survival. EEPF changes plant physio-chemical properties like volatile emission profile and secondary metabolite production to regulate insect pest defences. EEPF produce chitinases, laccases, amylases, and cellulases for plant defence. Recent studies focused on EEPF species' significance, isolation, identification and field application. Realizing their full potential is difficult due to insufficient mass production, storage stability and formulation. Genetic-molecular and bioinformatics can help to build EEPF-based biological control systems. Metagenomics helps study microbial EEPF taxonomy and function. Multi-omics and system biology can decode EEPF interactions with host plants and microorganisms. NGS (Next Generation Sequencing), comparative genomics, proteomics, transcriptomics, metabolomics, metatranscriptomics and microarrays are used to evaluate plant-EEPF relationships. IPM requires understanding the abiotic and biotic elements that influence plant-EEPF interaction and the physiological mechanisms of EEPF colonisation. Due to restricted research, there are hundreds of unexplored EEPFs, providing an urgent need to uncover and analyse them.